Corporate Environmental Strategic Management Analysis at PT. Sharia Permata Bank - Nur Sabila, Aliefya (PT Literasi Nusantara Publisher, 2023)
In Islamic banking, the level of productivity can be used as one of the benchmarks for evaluating performance. Productivity is one of the main indicators in assessing the competitive ability of Islamic banks. In a company, strategic management is an important role because it is the basis for making decisions for companies that are adjusted from the vision and mission that existed before. With strategic management, the company has a clear direction to monitor, control, analyze, and assess the success of implementing its operational strategy. The purpose of this study is to find out and analyze the strategies contained in the environment of Islamic banking companies and the strategic management of PT. Bank Permata Syariah.